Death of Neonates Aged 0-28 days in Pangkep Regency - Anas, Novitha Sri; Ahri, Reza Aril; Haeruddin, Haeruddin; Samsualam, Samsualam; Gobel, Fatmah Afrianty; Yusuf, Rezky Aulia; Muchlis, Nurmiati (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2023)
Background: Nation. Neonatal mortality is an indicator to assess the degree of public health. This study was conducted toanalyze the risk factors for neonatal death aged 0-28 days in Pangkep Regency in 2022. Method: This Study is an observational study with a case control research design. The population in this study was mothers who had babies died 0-28 days and all mothers who had babies lived aged 0-28 days in Pangkep Regency. The sample number of case groups was 40 respondents and the sample number of control groups was 40 respondents with a total of 80 samples. The sampling technique in this study is a non-probability sampling method, namely Purposive Sampling. Results: This study showed that significance values (1) mothers aged < 20 and > 35 years were 5.74 times more likely to experience neonatal death than mothers aged 20-35 years (CI95% = 5.74). (2) mothers with 1-time parity and 5 deliveries were 5.16 times more likely to have neonatal death than mothers with 2-4 deliveries (CI95%= 5.16) (3) mothers with a birth distance of < 1 year were 7.85 times more likely to have neonatal death than mothers with a birth distance of > 2 years (CI95%= 7.85) (4) access to health care was not at risk of neonatal death (CI95%= 0.81) (5) mothers with knowledge who were approximately 5.57 times more likely to experience neonatal death than mothers with good knowledge (CI95%= 5.57) (6) mothers with less than 4 times more than 5.57 times more risk of neonatal death than mothers with antenatal care examination> 4 times (CI95%= 52.76) (7) Antenatal care examination is the most risk factor for neonatal death with an Odd Ratio (EXP(B)) value of 12.767. Suggestion: It is hoped that health workers together with the community will further improve pregnancy screening to prevent high mortality of neonates.